Evaluation of the Military Spouse Employment Partnership Progress Report on First Stage of Analysis - Gonzalez, Gabriella C. (RAND Corporation, 2015)
In this first of two reports, RAND researchers assess whether and how The Military Spouse Employment Partnership addresses its objectives in supporting the employment of military spouses and closing the wage gap between military and civilian spouses. This report documents the first phase of research to help meet the 2015 National Defense Authorization Act requirement for a "report evaluating the progress of military spouse employment programs."